THE STRUCTURAL-DYNAMIC FEATURES OF PEDAGOGUES’ PERSONAL POTENTIAL - Sukhenko, Yana (PSYCHOLOGICAL JOURNAL, 2019)
The article examines the structural and dynamic characteristics of personal potential (PP) as a potential for pedagogues’ self-regulation. PP is considered as a system consisting of three functional structures: potential for self-determination, potential for realization, potential for preservation. The best formed basic components of the pedagogues PP are personal and social identity, copying strategies for problem solving, and conscious self-regulation of their activities. The indicators of life satisfaction, self-assessments of their happiness, tolerance to stress, reflexivity, self-organization, tolerance to uncertainty, meaningful life and the social support-seeking coping strategy are lower. The best developed structural components are the potential for preservation, which indicates that educators are better able to cope with pressure and threats than with situations requiring self-determination and goal implementation. The level of development and configuration of the structural components determine the overall typological PP range, which includes 7 types. Each type characterizes a certain stage of PP development, and their combination in the form of a dynamic cycloid model reflects PP structural and functional dynamics. The performed empirical study proves that PP growth and disclosure is related to the external situational context and occurs at two types of situation: either at increase of pressure, threats, continuous and increased uncertainty, restrictions on the way to the goals, associated with pre-crisis and crisis situations, or at pressure and threat reduction, uncertainty overcoming, emergence of possibilities for goal realization, associated with crisis overcoming, post-crisis or post-traumatic growth. In general, both types of conditions are characterized by existing transitional periods of personal development or development as personal changes. The level of personal potential development remains stable in the dichotomous situation of “realization - self-determination” against the background of low pressure and threats for a long time, i.e. in the conditions of stable development of a personality.